The Effects of Pricing, Promotion, and Service Quality on Purchasing Decisions in the Tourism Industry - Aslam Khitami; Cosmas Gatot Haryono; Fahrul Riza (PROCURATIO: Jurnal Manajemen & Bisnis, 2026)
Purpose – This study examines the effects of price, promotion, and service quality on customers' purchase decisions in the tourism transportation service sector. The study aims to identify the relative importance of these marketing factors in influencing consumer decision-making within experience-based service contexts. Design/method/approach – A quantitative explanatory research design was employed using survey data collected from 100 customers through a structured questionnaire measured on a five-point Likert scale. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Findings – The results reveal that promotion and service quality have significant positive effects on purchase decisions, whereas the effect of price is positive but statistically insignificant. Service quality emerges as the strongest predictor of purchase decisions, indicating that customers place greater emphasis on service experience and promotional effectiveness than on price when selecting tourism transportation services. The structural model explains 54.7% of the variance in purchase decisions (R² = 0.547), suggesting moderate explanatory power. Implications – The findings extend the perceived value perspective by demonstrating that value perceptions in tourism transportation are driven primarily by service quality and promotional effectiveness rather than price considerations. The results also provide managerial insights for tourism transportation providers to strengthen competitiveness by prioritizing service excellence and targeted promotional strategies instead of competing mainly through price reductions. Novelty/Originality – The novelty of this study lies in its finding that price does not significantly influence purchase decisions in the tourism transportation context, in contrast to previous studies in public transportation. This outcome is driven by the demographic characteristics of respondents-particularly their productive age and collective purchasing patterns-which reduce price sensitivity and elevate the importance of service quality. The study further confirms that service quality is the most dominant factor within family-owned bus tourism enterprises, thereby enriching the understanding of consumer behavior in high-involvement, experience-based services.